Perceptions of Reporting on Islamization by Malaysia’s Popular Alternative Media: An Accurate Representation? - Nor, Murni Wan Mohd (Journal of Muslim minority affairs, 2022)
Malaysia has been described as a country which successfully implements a “moderate” Islam. However, sentiments amongst Malaysians, particularly on social media reveal tensions regarding racial and religious matters which has intensified amidst the changing political landscape of the nation. Islamization remains a controversial issue as reflected in the public’s mixed reaction to the government’s unofficial Islamization policy. This paper discusses the representation of Islamization by Malaysia’s popular alternative media via in-depth interviews with experts in related fields. The findings indicate that most informants perceived that media reporting of Islamization is framed negatively. This is aggravated by the media’s usage of strong language, negative generalizations, inappropriate pictures and general lack of sensitivity to racial and religious issues. Implications of these findings are discussed.